If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = -4x + -14 Reorder the terms: -2 = -14 + -4x Solving -2 = -14 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -2 + 4x = -14 + -4x + 4x Combine like terms: -4x + 4x = 0 -2 + 4x = -14 + 0 -2 + 4x = -14 Add '2' to each side of the equation. -2 + 2 + 4x = -14 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = -14 + 2 4x = -14 + 2 Combine like terms: -14 + 2 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 15(x+1)=3x(4+5) | | -11x-10y=175x-7y=50 | | -6-22= | | 2x+3y=38 | | 2x+3y=36 | | -11x-10y=17 | | -3(2s-6)-18=-3(7s+1)-4 | | 7=3(2x-8) | | 7x+8=2x+58 | | 2(z-6)-(5+7z)=-10z | | 2(2x+3)-7x=23-5(x+3x) | | 5x=11x-23 | | (5x+2)-(3x-1)= | | 6x-28=2x+76 | | -3n+11=-13 | | 10+6x+3x=19 | | 2(2x+3)-7x=18+5(x+2x) | | 3c-4=27 | | -3v^2-20v+12=0 | | 6m-4=m+11 | | 19+m=100 | | 125x^3+343=0 | | 10+3x=7x-14 | | x+23=79 | | -11(3-2a)=2(12a+4) | | 3m-2m(m+7)=2m+14 | | -7(z+6)-(6z-9)=-14z | | f=4(4)+3(10) | | 3x+4y=40 | | 4x+8=2x+46 | | 4(2x-10)=20 | | a=0.5(15+3) |